An educational intervention to improve knowledge and attitudes to develop healthy dating relationships among undergraduates in Western Province - Eranga Fernando; Aindralal Balasuriya (Journal of the College of Community Physicians, 2022)
Introduction Dating violence is a major public health issue which has failed to gain recognition in the country. It was never studied in the local setting despite the higher prevalence/ incidence reported in other countries.